Effects of surface characteristics on condensation - Chan, Tow Kai (Nanyang Technological University, 2020)
Heating, ventilating and air conditioning (HVAC) uses the concept of condensation for the industry. Daily application of condensation includes the possibility of harnessing water from the atmosphere which involves condensing the water vapour present in the air into clean and drinkable water for the masses. This method of harnessing water from the atmosphere is relatively simple in terms of technology and cost effective. In this project, different surfaces will be fabricated via physical and chemical spray treatment. The various surfaces will then be analysed to determine the effects of surface characteristics on condensation. Under the consideration of parameters such as contact angle, surface roughness and patterning. 18 specimens were fabricated with various surface characteristics: 8 of the specimens were fabricated to mimic the surface characteristics of a plant leaf with vary angles of hydrophilic tracks. Preliminary experiments were conducted to determine the effects of each patterning based on their contact angles and average surface roughness. Subsequent experiments were then conducted to compare the different rates of condensation yield from each specimen. All the experiments were conducted at a controlled atmosphere (30℃, 90% relative humidity). The bioinspired patterning constructed on the specimen surface seen an overall improvement of condensate collection rate up to 300% (as compared to the control case which had zero surface alteration). The most desirable specimen was ‘Leaf 2’ which managed to yield 6.2ml of condensate per hour from the atmosphere.